Prediction of delamination strength at interface between thin film and substrate by cohesive zone model - Truong, Do Van; Hirakata, Hiroyuku; Katamura, Takayuki (Vietnam Journal of Mechanics, 2006)
An electronic device consists of multi-layered submicron-thick films, and delamination often takes place at an interface edge because of the stress singularity near the edge. Since the stress singularity at an interface edge depends on the edge shape, the fracture mechanics concept cannot be used to compare the delamination strength between the components with different shapes. This paper aims to predict the delamination strength at the interface edge with arbitrary shape using a cohesive zone model. Two different experiments are conducted for a gold thin film on a silicon substrate to calibrate the cohesive law. The validity of the approach is then discussed.